Online Educational Tool to Promote Bone Health in Cancer Survivors. Issue 10 (3rd October 2017) - des Bordes, Jude K. A.; Suarez-Almazor, Maria E.; Volk, Robert J.; Lu, Huifang; Edwards, Beatrice; Lopez-Olivo, Maria A.
Abstract : Osteoporosis burden is significant in cancer survivors. Websites providing health information abound, but their development, quality, and source of information remain unclear. Our aim was to use a systematic and transparent approach to create an educational website on bone health, and to evaluate its potential to improve knowledge, self-management, and awareness in prostate cancer (PCa) and breast cancer (BCa) survivors. Guided by the Health Belief Model, we created a website using international standards and evaluated it in 10 PCa and 10 BCa survivors with self-administered questionnaire before, after, and 1 month after navigating the website. The mean scores on the knowledge questionnaire at baseline, postintervention and 1 month were, respectively, 5.1 (±2.0), 6.9 (±2.5), and 6.7 (±2.4), p  < .008, in PCa and 3.4 (±2.7), 7.6 (±3.0), and 6.5 (±3.8), p   = .016, in BCa survivors. Acceptability ratings ranged from 60% to 100%. Participants found the website useful, helpful, and able to raise bone health awareness. Our website improved bone health knowledge in both PCa and BCa survivors. A systematic and transparent approach to the development of online educational websites could result in a tool capable of meeting the educational needs of targeted consumers. Cancer survivors could benefit from proven online educational tools.